LEARNING ENGLISH DURING THE PANDEMIC IN MI SUNAN AMPEL USED BLENDED LEARNING METHOD - Imro Atus Soliha; Agustiarini Eka Dheasari; Ulil Hidayah; Della Yunita (AL IBTIDAIYAH: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2021)
Learning from home (LFH) policy during COVID-19 pandemic effected to the new problems for students in elementary level. The policy has changed many aspects in the learning process. Between teachers and students were no longer face-to-face in the classroom, teaching and learning process starting to be integrated with online activities. This study aimed to describe learning English during the pandemic in MI Sunan Ampel Tongas used blended learning method. The study used a qualitative case study method. The research instruments were teachers and students of five grade in MI Sunan Ampel who already applied blended learning method in learning process during the pandemic. The results told that good collaboration between teachers, students, and parents can overcome any difficulties in adapting the blended learning method during a pandemic. The implementation of blended learning method in learning English force teachers to be more creative and innovative in providing English learning platform in the form of video, games or power point. Students’ activeness and family support also give a good impact during online learning activities.